CRISPR/Cas tools for enhancing the biopreservation ability of lactic acid bacteria in aquatic products - Dong, Huina; Wang, Huiying; Fu, Shaoping; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2022)
Lactic acid bacteria (LAB) plays a crucial function in aquatic products biopreservation as it can inhibit many bacteria, in particular the specific spoilage organisms (SSOs) of aquatic products, by competing for nutrients or producing one or more metabolites which have antimicrobial activity, such as bacteriocins. Lactobacillus spp. and Lactococcus spp. are the most commonly used LABs in aquatic products preservation. The improvement of gene editing tools is particularly important for developing new lactic acid bacteria strains with superior properties in aquatic products biopreservation. This review summarized the research progress of the most widely used CRISPR/Cas-based genome editing tools in Lactobacillus spp. and Lactococcus spp.. The genome editing tools based on homologous recombination and base editor was described. Then, the research status of CRISPRi in transcriptional regulation was reviewed briefly. This review may provide a reference for the application of CRISPR/Cas-based genome editing tools in other lactic acid bacteria species.